Comprehensive Genome-Wide Identification and Expression Profiling of Eceriferum (CER) Gene Family in Passion Fruit (Passiflora edulis) Under Fusarium kyushuense and Drought Stress Conditions - Rizwan, Hafiz Muhammad; Waheed, Abdul; Ma, Songfeng; Li, Jiankun; Arshad, Muhammad Bilal; Irshad, Muhammad; Li, Binqi; Yang, Xuelian; Ali, Ahmad; Ahmed, Mohamed A. A.; Shaheen, Nusrat; Scholz, Sandra S.; et al. (Frontiers in Plant Science, 2022)
Plant surfaces are covered with cuticle waxes and are the first barrier between the plant and environmental stresses. Eceriferum (CER) is an important gene family involved in wax biosynthesis and stress resistance. In this study, for the first time, thirty-four CER genes were identified in the passion fruit (Passiflora edulis) genome. The cis-element analysis provides insight into the possible roles of PeCER genes in plant growth, development, and stress responses. Syntenic analysis revealed that gene duplication played an important role in the expansion of the PeCER genes and underwent a strong purifying selection. In addition, twelve putative ped-miRNAs were identified to target sixteen PeCER genes and PeCER6 was the most targeted by four miRNAs, including ped-miR157a-5p, ped-miR164b-5p, ped-miR319b, and ped-miR319l. Potential transcription factors (TFs) including ERF, AP2, MYB, bZIP, etc were predicted and visualized in a TF regulatory network interacting with PeCER genes. GO and KEGG annotation analysis revealed that PeCER genes were highly related to fatty acid, cutin and wax biosynthesis, plant-pathogen interactions, and stress responses. Transient expression assay of PeCER32 in onion epidermal cells was localized to the plasma membrane. qRT-PCR expression results showed that most of the PeCER genes including PeCER1, PeCER11, PeCER15, PeCER17, and PeCER32 were upregulated under drought and Fusarium kyushuense stress conditions compared to controls. These findings provide the foundation for further studies on the function of PeCER genes to further facilitate the genetic modification of passion fruit wax biosynthesis and stress resistance.